Using multicriteria analysis and fuzzy logic for project portfolio management - Agápito, Andrezza de Oliveira; Vianna, Marcilene de Fátima Dianin; Moratori, Patrick B.; Vianna, Dalessandro Soares; Meza, Edwin Benito Mitacc; Matias, Italo de Oliveira (Brazilian Journal of Operations & Production Management, 2019)
Goal: to propose a hybrid method, combining AHP and Fuzzy, for project portfolio management. Originality/value: this paper meets the positive characteristics of both methods, adequately weighing the criteria and contemplating process subjectivity. Limitations that exist in both methods, such as the maximum number of alternatives and the difficulty of inserting new alternatives at the end of the process, are overcome. Design/methodology/approach: the AHP is applied for determining the criteria weights and fuzzy is used to compare the alternatives for each criterion. Results: the results show that the proposed hybrid method allows the ranking of many alternatives and provides higher reliability for decision makers. It must be noted that the system is fed by performance indicators, which minimize the subjectivity in decision-making—an important characteristic in the technology management. Moreover, the results provide the possibility of changing the number of projects at any time without influencing the outcome. Practical implications: the proposed hybrid method can be used in different problems that have many alternatives or subjectivity.